The Role of Flexible Work Arrangements in Enhancing Employee Well- Being and Productivity: A Study on SDG 8 Implementation in Tech Companies - Loh, Cheau Wei; Cheng, Mui Li (INTI International University, 2024)
Employee well-being and productivity have come to the forefront of human resource management (HRM) in the technology sector. This trend is coherent with the goals of Sustainable Development Goal 8 (SDG 8), which promotes sustained, inclusive, and sustainable economic growth, full and productive employment, and decent work for all (Küfeoğlu, 2022). The high-pressure, fast-paced environments endemic to the tech industry align with the intent to enhance workplace environments to promote mental health and overall well-being in pursuit of SDG 8. According to Warmate et al. (2021), this mainly includes allowing for flexible work arrangements (FWAs), such as remote work, flexible hours, and compressed workweeks. The pandemic has forced the tech industry to adopt FWAs; in some cases, this might even have been a positive development, particularly regarding employee satisfaction and mental health, which are good for business. This study aims to address SDG 8 by examining the implementation of FWAs in tech companies as an avenue for improving the well-being and performance of employees. The application of theories like Self-Determination Theory (SDT) highlights how FWAs fulfil basic psychological needs such as autonomy, competence, and relatedness, thereby boosting engagement and motivation among employees.